Secreted in Xylem Genes: Drivers of Host Adaptation in Fusarium oxysporum - Jangir, Pooja; Mehra, Namita; Sharma, Karuna; Singh, Neeraja; Rani, Mamta; Kapoor, Rupam (Frontiers in Plant Science, 2021)
Fusarium oxysporum (Fo) is a notorious pathogen that significantly contributes to yield losses in crops of high economic status. It is responsible for vascular wilt characterized by the browning of conductive tissue, wilting, and plant death. Individual strains of Fo are host-specific (formae speciales) and approximately 150 forms have been documented so far. The pathogen secretes small effector proteins in the xylem, termed as Secreted in Xylem (Six), that contribute to its virulence. Most of these proteins contain cysteine residues in even numbers. These proteins are encoded by SIX genes that reside on mobile pathogenicity chromosomes. So far, 14 proteins have been reported. However, formae speciales vary in SIX proteins profile and their respective gene sequence. Thus, SIX genes have been employed as ideal markers for pathogen identification. Acquisition of SIX-encoding mobile pathogenicity chromosomes by non-pathogenic lines, through horizontal transfer, results in the evolution of new virulent lines. Recently, some SIX genes present on these pathogenicity chromosomes have been shown to be involved in defining variation in host-specificity among formae speciales. Along these lines, the review entails the variability (formae speciales, races, and vegetative compatibility groups) and evolutionary relationships among members of F. oxysporum species complex (FOSC). It provides updated information on the diversity, structure, regulation, and (a)virulence functions of SIX genes. The improved understanding of roles of SIX in variability and virulence of Fo has significant implication in establishment of molecular framework and techniques for disease management. Finally, the review identifies the gaps in current knowledge and provides insights into potential research landscapes that can be explored to strengthen the understanding of functions of SIX genes.